Factors Determining Regional Tax Revenue: Case Study of Districts and Cities in West Nusa Tenggara 2019–2023 - Lesi Anaputri; M. Irwan; Eka Agustiani (Future Techno-Science, 2025)
This study aims to analyze the factors that influence District/City Regional Taxes in NTB in 2019-2023. This research method is quantitative research with an associative approach. This study uses secondary data obtained from the website of the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance and the Central Statistics Agency (BPS) of West Nusa Tenggara Province. The variables used in this study are Population, Per Capita Income and GRDP. To determine the regression model, three approaches are used, namely the Common Effect Model, Fixed Effect Model and Random Effect Model. The selection of the best model is carried out through three tests, namely the Chow Test (likelihood test), the Hausman Test and the Lagrange Multiplier Test. For the calculation using the Classical Assumption Test consisting of the Multicollinearity Test and the Heteroscedasticity Test. And Hypothesis Test with Partial Test (t test), Simultaneous Test (f test) and Coefficient of Determination (R2). The results of the study indicate that the population variable has a negative and insignificant effect. The per capita income variable has a negative and significant effect, and the GRDP variable has a positive and significant effect on regional taxes in regencies/cities in NTB. Simultaneous calculations provide results that the population, per capita income and GRDP variables have a positive and significant effect on regional taxes with a large effect of 84.89 percent, and the remaining 15.11 percent is influenced by other variables not examined in this study or other variables outside the model.